“Nutridi”: Modifikasi timbangan pangan digital sebagai alat pendukung pembelajaran gizi - Dina Fadhilah; Diana Andriyani Pratamawati; Aprilia Alua (Poltekkes Kemenkes Yogyakarta, 2025)
Misestimating portion sizes of food consumed will affect the quality of the estimate and result in inaccurate nutrient intake. Conventional digital food scales only measure body weight without listing nutritional values, thus limiting their usefulness in health education and promotion. This study aims to develop and test Nutridi, a modified digital food scale equipped with nutritional reference values, as a tool to support nutrition education. Research Methods This research is a quantitative study with a research and development (R&D) design at Poltekkes Kemenkes Yogyakarta between April and October 2022. The object of this study is the Nutridi digital scale, developed by integrating food composition data into the digital weighing system. Data processing using the Stata application began with a normality test using the Kolmogorov-Smirnov test and then a paired t-test. The results of weighing 62 food ingredients showed that the Nutridi digital scale was proven to be precise (CV 0%) and accurate equivalent to the Camry digital scale (mean difference ?1 g), The normality test on the distribution of differences between the Nutridi digital scale and the Camry digital scale (pooled, n = 186) with Kolmogorov–Smirnov showed deviations from the normal distribution (mean diff 0.0430 g; SD 0.2034 g; D = 0.5407; p <0.001), which was likely influenced by the large number of identical difference values ??(ties; e.g. 0 g or ±1 g) due to the limited resolution of the measuring instrument. However, the paired t-test per ingredient showed that for ingredients with measurement variations, there was no significant difference between the two scales (p>0.05), while for ingredients with all identical replicates between tools, the t-statistic was not calculated because the variance was zero which practically indicated that the results of both tools were exactly the same. In conclusion, the Nutridi digital scale has good precision and accuracy and is suitable for use as a learning tool in food weighing practicums at the Nutrition Department of the Ministry of Health's Polytechnic of Health, as well as for household use. Further research is needed to validate its accuracy, improve its usability, and expand its food database for broader applications.